The Influence of Work Environment And Job Stress on The Performance of Career Sailors on Board With Job Satisfaction As A Intervening Variable (A Study on Sailors Participating in Navigation Skill Training at Politeknik Ilmu Pelayaran Semarang) - Norma Rahmatika Hadi Armika; Tristiana Rijanti (Green Publisher Indonesia, 2024)
The research aims to examine the influence of the work environment and job stress on the performance of seafarers in their careers aboard ships, with job satisfaction as an intervening variable. The method applied is a census. The research population consists of all sailors participating in maritime skills training at the Maritime Polytechnic of Se-marang, totaling 90 people. Data collection technique involves surveys. The analysis process includes instrument testing, model testing, F-test, multiple regression test, and hypothesis testing. The research results indicate that: (1) the work environment has a significantly positive influence on job satisfaction; (2) job stress has a significant-ly negative influence on job satisfaction; (3) the work environment has a significantly positive influence on performance; (4) job stress does not have a significant influence on performance; (5) job stress indirectly influences performance negatively through job satisfaction.